Fabrication of Large-Area High-Resolution Templates by Focused Ion Beam Combined with Colloidal Nanoparticle Dimer Deposition for SERS Substrates - Ignatane, Liga; Ignatans, Reinis; Prikulis, Juris; Trausa, Annamarija; Tipaldi, Ciro Federico; Vanags, Edgars; Zubkins, Martins; Smits, Krisjanis; Sarakovskis, Anatolijs (MDPI, 2024)
This article presents an examination of well-controlled patterns created using a Ga+-based focused ion beam (FIB) on glass, while silicon substrates were used to evaluate the FIB performance by its achievable feature size versus time constraints. The pattern creation on glass was developed with the aim of studying potential surface-enhanced Raman spectroscopy (SERS) applications. Furthermore, the FIB was used to create dimer systems of periodically and randomly positioned dumbbell-shaped pits on the glass (each dimer occupies an area of 203 × 87 nm2). By following the bitmap pattern files, the FIB ensured there was 3000 dimer fabrication over a 20 × 20 μm2 large area, with a pit size and position variation below 10 nm. The article highlights that FIB can be used for precise large-area nano-fabrication. The gold nanoparticle dimers were formed on the prepatterned surface via capillary force-assisted deposition. The fabricated nanostructures were tested in SERS measurements. The enhancement factor for Rhodamine B molecule reached ~105, demonstrating the potential application of the method to create nanostructures in the sensor domain. © 2024 by the authors. --//-- This is an open-access article Ignatane, L.; Ignatans, R.; Prikulis, J.; Trausa, A.; Tipaldi, C.F.; Vanags, E.; Zubkins, M.; Smits, K.; Sarakovskis, A. Fabrication of Large-Area High-Resolution Templates by Focused Ion Beam Combined with Colloidal Nanoparticle Dimer Deposition for SERS Substrates. Nanomaterials 2024, 14, 1784. https://doi.org/10.3390/nano14221784 published under the CC BY 4.0 licence.
The financial support of the European Regional Development Fund project Nr. 1.1.1.1/21/A/053, and the financial support of the LZP project VPP-EM-FOTONIKA-2022/1-0001, realized at the Institute of Solid State Physics, are greatly acknowledged.. Authors acknowledge the Institute of Solid State Physics of the University of Latvia, which as a center of excellence has received funding from the European Union framework program Horizon 2020 H2020-WIDESPREAD-01-2026-2017-TeamingPhase2 within the framework of grant agreement No. 739508 of the CAMART2 project.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; dimers; focused ion beam; nanostructure fabrication; plasmonics; SERS